1994
DOI: 10.1029/93jb03125
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of large events on a dynamical model of a fault

Abstract: We present results for long term and intermediate term prediction algorithms applied to a simple mechanical model of a fault. We use long term prediction methods based, for example, on the distribution of repeat times between large events to establish a benchmark for predictability in the model. In comparison, intermediate term prediction techniques, analogous to the pattern recognition algorithms CN and M8 introduced and studied by Keilis-Borok et al., are more effective at predicting coming large events. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…With A we are able to predict 90% of the large events, with alarms which occupy 15% of the total space-time volume (Fig. 3), which corresponds to alarms which occupy significantly smaller time intervals than the average duration of small scale seismicity prior to large events 20 in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With A we are able to predict 90% of the large events, with alarms which occupy 15% of the total space-time volume (Fig. 3), which corresponds to alarms which occupy significantly smaller time intervals than the average duration of small scale seismicity prior to large events 20 in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20] a detailed study of predictability of the UBK model revealed that among a set of precursors, the two most effective are activity A= # earthquakes, and a new measure which is a better measure of the development of spatial correlations. This new measure, which we call active zone size AZS, is defined to be: AZS = # blocks which have slipped (independent of the number of times) in each space-time window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors used the simulated catalogs to study in greater detail the performance of pattern recognition methods tested already on observed catalogs and other models [96,107,108,109,110,111,112,113,114], devised new methods, and experimented with combination of different individual premonitory patterns into a collective prediction algorithm.…”
Section: Bifurcation Diagrammentioning
confidence: 99%
“…While these models do not have the complete set of earthquake behaviors, they are nevertheless rich enough to use in a variety of ways. We can, for example, compare and hone our techniques and pose new questions in a context where limited catalogues and statistics are not an issue [Pepke et al, 1994] before tackling real catalogues [Kossobokov and Carlson, 1995].…”
Section: Introductionmentioning
confidence: 99%